Developing order release and scheduling model for order picking - Lehtinen, Tuukka (My University, 2024)
Manufacturing firms aim at fulfilling the customer demand so that the materials and capacities are managed and planned based on the customer needs. The goal is that the supply and demand are met at least approximately while keeping the quality at a high level and ensuring the cost efficiency of the logistics operations. One commonly used approach to attain these goals is production planning and control which includes functions such as order release and scheduling. The purpose of this study is to design a new order release and scheduling model for order picking, which is going to be implemented in one of the warehouses of the case company of this study. In the new process models involved stakeholders, their roles and different steps of the processes are defined, as well as example view of the scheduling dashboard is created. The new order release and scheduling models were piloted in another warehouse of the company and in this study the pilot model is evaluated, and based on that, new improved order release and scheduling models aiming at high on-time delivery rate and minimal waste in the processes are created. The new improved models can thus be implemented in the target warehouse. The study follows design science research approach which aims at developing a technical solution for business problems in real life. First, the pilot model including the motivation, designing and implementation of the models is presented to familiarize the reader with the initial situation of the models. After that the pilot model is evaluated in a workshop including stakeholders of the processes which serves as a primary data of this study. Then based on the workshop discussion and theoretical framework of the study, new improved models are created. The designed solution is new process models where tasks, communication and information flow of the order release process are simplified, and scheduling process and scheduling dashboard enabling scheduling of better quality are created. The new order release process contains less waste and enables achieving high on-time delivery rate better. Order scheduling process and the dashboard used for scheduling enable better planning of resource utilization and flexibility. However, in this research no measurement is done if the performance of the processes is getting better. Therefore, it is suggested that future research is done to measure process performance and evaluate and improve the processes even further. Teolliset yritykset pyrkivät vastaamaan kysyntään niin, että materiaaleja ja kapasiteettia hallitaan ja suunnitellaan asiakkaiden tarpeen perusteella. Tavoitteena on, että kysyntä ja tarjonta vastaisivat ainakin suunnilleen toisiaan, pitäen samalla huolta korkeasta laadusta sekä logististen toimintojen kustannustehokkuudesta. Yksi usein käytetty lähestymistapa on tuotannonsuunnittelu ja -ohjaus, joka sisältää toimintoja, kuten tilausten vapautus sekä tilausten aikataulutus. Tämän tutkimuksen tarkoituksena on suunnitella uusi tilausten vapautus ja tilausten aikataulutus -malli tilausten keräilyyn, joka tullaan ottamaan käyttöön yhdessä tutkimuksen kohdeyrityksen varastoista. Uudessa prosessimallissa on kuvattu kaikki mukana olevat sidosryhmät, heidän roolinsa sekä eri toimenpiteet, jonka lisäksi suunnitellaan esimerkkinäkymä tilausten aikataulutus -ohjelmaan. Tilausten vapautus ja aikataulutus prosessit pilotoitiin aiemmin yrityksen toisessa varastossa ja tässä tutkimuksessa pilottimallia arvioidaan ja sen perusteella luodaan uudet parannetut tilausten vapautus ja aikataulutus mallit, jotka tähtäävät korkeaan toimitusvarmuuteen sekä minimaaliseen hukkaan. Uudet parannetut mallit voidaan täten ottaa käyttöön kohdevarastossa. Tutkimuksessa käytetään design science -tutkimusmetodia, jonka pyrkimyksenä on luoda tekninen ratkaisu oikeisiin liike-elämän ongelmiin. Ensiksi pilottimalli sisältäen tutkimuksen motivaation, mallin suunnittelun sekä täytäntöönpanon, esitellään lukijalle tämän tutustuttamiseksi prosessimallien lähtötilanteeseen. Tämän jälkeen pilottimalli arvioidaan prosessiin kuuluvien sidosryhmien kanssa työpajassa, joka toimii työn tutkimusdatana. Uudet parannetut prosessimallit luodaan siten käytyjen työpajakeskustelujen sekä teoreettisen viitekehyksen perusteella. Tutkimuksen tuotos on uudet prosessimallit, jossa tilausten vapautuksen toimenpiteet, kommunikaatio sekä tiedonvirtaus ovat yksinkertaistettu, ja laadukkaamman aikataulutuksen mahdollistava tilausten aikataulutus prosessi ja -ohjelman esimerkkinäkymä on luotu uudelleen. Uusi tilausten vapautusmalli sisältää vähemmän hukkaa ja mahdollistaa korkean toimitusvarmuuden tavoittelemisen. Tilausten aikataulus prosessi sekä -ohjelma mahdollistavat paremman resurssiensuunnittelemisen sekä joustavuuden. Tutkimuksessa ei kuitenkaan mitata, yltävätkö suunnitellut prosessit parempaan suorituskykyyyn. Tämän takia ehdotetaankin, että lisätutkimusta tehtäisiin, jotta prosessien suorituskykyä voitaisiin mitata sekä arvioida ja kehittää prosesseja entistäkin paremmiksi.
Keywords: logistics; production planning; lean manufacturing; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management